Hypnosis for the Management of Anticipatory Nausea and Vomiting - Kravits, Kathy G. (J Adv Pract Oncol, 2015)
CASE STUDYBJ is a 34-year-old woman who was diagnosed with metastatic breast cancer. She was treated with surgical removal of the primary tumor and sentinel node biopsy. Following surgery, she received chemotherapy. She was given antiemetic therapy prior to and immediately following chemotherapy. She began to experience significant and persistent nausea with intermittent episodes of vomiting after the second cycle of chemotherapy. She completed her chemotherapy but still experienced nausea and vomiting in response to several cues, such as smelling food cooking and going to the hospital. Her nausea and vomiting resulted in segregation from her family during meal time, which negatively impacted her quality of life. A hypnosis consultation was requested, and BJ was cooperative. She reported feeling very nauseated at the time of the interview. Hypnosis was discussed; her questions were answered, and the potential risks and benefits of hypnosis were reviewed. She agreed that she would like to try hypnosis. A hypnosis assessment was conducted and revealed that she had a history of profound motion sickness and severe, chronic childhood trauma associated with feelings of anxiety and hypervigilance. The therapeutic suggestions that were used with BJ included hypnotic suggestions for relaxation and removal of discomfort. A metaphor describing the central processing of the anticipatory nausea and vomiting as a thermostat that could be adjusted to reduce and eliminate the sensation was used to suggest that she could control her perceptions and in turn control the nausea. Posthypnotic suggestions included that at the earliest awareness of discomfort, rubbing the throat would eliminate that discomfort, and cooking aromas would be transformed into her favorite fragrance. Reversal went smoothly, and BJ reported satisfaction with the experience. BJ experienced significant reduction in symptoms after the first session. She had two more sessions, at which time she was able to eat with her family and go to the clinic without discomfort. She was provided a CD with a recording of her hypnosis script to reinforce the face-to-face intervention. She continues to be symptom-free 3 months after treatment with hypnosis.